Manfaat Brand Positioning Pada Laundry Bersih Total Di Kelurahan Tenggilis Mejoyo Kota Surabaya - Ilhan Samudra Fattah; Sugito Sugito (jurnal ABDIMAS Indonesia, 2023)
Micro, Small and Medium Enterprises (MSMEs) play an important role in economic growth in Indonesia. Positioning Branding or brand identity is very necessary for every business, but in reality, few MSME players pay attention to brand positioning or brand identity themselves. Therefore, the purpose of this article is to provide information regarding the benefits obtained by paying attention to branding positioning for MSME players. By paying attention to brand positioning, MSME players can understand the benefits of their own brand positioning and hopefully be able to compete. We hope that this article can help solve the problems of MSME players in terms of their own brand positioning.